Princely graves from Kleinklein in Styria, Austria - Markus Egg (Arheološki Vestnik, 2019)
The princely graves in the Hartnermichelkogel 1 and 2, Pommerkogel and Kröllkogel tumuli form a burial ground separate from the rest of the Early Hallstatt necropolis located below the hillfort at Burgstallkogel near Kleinklein. They are the largest and most richly furnished tumuli of the Eastern Hallstatt culture, which spread across Austrian and Slovenian Styria, in north-eastern Croatia and western Pannonia. The contribution presents the chronological succession of the tumuli, their construction, furnishings and grave goods. It provides an outline of the funerary ritual of the elite buried there in the span of a century and a half, and defines the social status of the deceased as that of kings rather than chieftains.